The second coming - Davies, Russell T; Shergold, Adrian; Eccleston, Christopher; Sharp, Leslie; Apison, Annabelle; Armitage, Peter; Benton, Mark; Bhatti, Ahsen; Harrison-Baxter, Ann; Shindler, Nicola; Red Production Company; Sony Music Entertainment, Inc; et al. (New York : Sony ; Los Angeles, Calif. : Distributed by Shout! Factory, 2003)
Steve Baxter, a mild-mannered, Manchest pub-crawler is called upon one night to his true destiny as the second Son of God. After a couple of convincing miracles, the world looks to Steve for guidance, but he give mixed signals: on one hand he calls for a Third Testament to establish a foundation for living in the modern age; on the other, he predicts and imminent Judgement Day. The confusion cause mass mayhem, and Steve's disciples, try to make sense of the conflict while preventing devils, in human form, from undermining his mission
Originally presented as a two part mini-series on BBC and BBC America
Includes special features: Russell T. Davies and Adrian Shergold commentary. Exclusive 37 minutes of deleted scenes plus some outtakes
Produced by Ann Harrison-Baxter with executive producers Nicola Shindler and Russell T. Davies
Starring Christopher Eccleston and Lesley Sharp, Annabelle Apison, Peter Armitage, Mark Benton, Ahsen Bhatti
MPAA rating: Not rated
DVD, video aspect ratio 16:9; Dolby digital
Keywords: Judgment Day -- Drama; Son of God -- Drama; Video recordings for the hearing impaired; Television mini-series